Identification of Geothermal Prospect Zones in Bittuang Area Based on Remote Sensing and Geochemical Data - Imran, Ali (CV Insight Publisher, 2024)
The research location is in the Bittuang area located in Tana Toraja Regency, South Sulawesi, Indonesia. The high level of risk of geothermal drilling at the exploration stage requires integrated geological and geochemical analysis. The integrated analysis is poured into the geothermal system conceptual hypothesis model used to identify geothermal prospect zones. This study focuses on Remote Sensing and Geochemistry methods. To identify the existence of geological structures and lithological interpretation as well as surface manifestations, Remote Sensing is used. Based on the results of Remote Sensing interpretation, the research area consists of 13 rock units of Tertiary to Quaternary age with geological structures in the form of normal faults and horizontal faults that are relatively north-northwest-southeast east and southwest-northeast. The manifestations present on the surface consist of traces of fumaroles and hot springs. The hot springs consist of the chloride type in the centre of the site and the bicarbonate type in the south of the study area. The results of geothermometer calculations of geochemical data obtained a subsurface temperature of 176 -198 °C, which is categorized as a moderate to high temperature geothermal system. The geothermal conceptual model built based on the integration of geological and geochemical data shows that the geothermal system is influenced by volcanic activity and controlled by the structure of the research area. The area of the prospect is about 4 km2 with the up-flow area in the middle of the area while the outflow is in the South.